Custo social do desmatamento nos biomas brasileiros - Jéssica Suarez Campoli; Matheus Stivali (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Determining the social cost of deforestation in each Brazilian biome is an important task to support public policy and the decision-making process. This work summarizes the economic valuation estimates of vegetation cover found in the literature for each Brazilian biome. A systematic literature review was carried out identifying the values estimated by the total economic value (TEV) method for each Brazilian biome. For the two biomes in which no estimate was found (Cerrado and Pampa), we produced estimates following a procedure common in the literature. Subsequently, different estimates were put together to establish a range of values for each Brazilian biome in USD per hectare at 2020 prices. This resulted in the following ranges for: the Amazon (655.20- 5,238.33 USD/ha), Cerrado (426.02-4,795.07 USD/ha), Atlantic Forest (3,504.41-6,565.24 USD/ ha), Caatinga (3,239.81-3,505.97 USD/ha), Pampa (426.02-4,795.07 USD/ha) and Pantanal (9,830.52-10,196.17 USD/ha). This summary of valuations besides subsidizing government policies and strategies on the environmental agenda can help to improve decision-making by highlighting the implicit cost of damage to different biomes.
10419/284898
Keywords: D61; N56; Q20; 330; social cost; deforestation; cost-benefit analysis; total economic value